2017
DOI: 10.1038/s41525-017-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing as a platform for pharmacogenetic genotyping: a pediatric cohort study

Abstract: Whole-genome sequencing and whole-exome sequencing have proven valuable for diagnosing inherited diseases, particularly in children. However, usage of sequencing data as a pharmacogenetic screening tool to ensure medication safety and effectiveness remains to be explored. Sixty-seven variants in 19 genes with known effects on drug response were compared between genome sequencing and targeted genotyping data for coverage and concordance in 98 pediatric patients. We used targeted genotyping data as a benchmark t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
4
48
0
1
Order By: Relevance
“…Similarly, mitochondrial genomes in each cell may not all be identical, and a variant in only a subset is called heteroplasmy. 14,15 To gain further insight into the spectrum of genomic variation, we assessed the disease-causing potential of all disease-associated variants in accordance with guidelines of the American College of Medical Genetics and Genomics. Variants were sorted into categories of standard terminology: "benign," "likely benign," "variant of uncertain significance" (VUS), "likely pathogenic" or "pathogenic," 16 by applying specified information from the published literature and various disease-and populationbased databases.…”
Section: Box 1: Human Genome Variationmentioning
confidence: 99%
“…Similarly, mitochondrial genomes in each cell may not all be identical, and a variant in only a subset is called heteroplasmy. 14,15 To gain further insight into the spectrum of genomic variation, we assessed the disease-causing potential of all disease-associated variants in accordance with guidelines of the American College of Medical Genetics and Genomics. Variants were sorted into categories of standard terminology: "benign," "likely benign," "variant of uncertain significance" (VUS), "likely pathogenic" or "pathogenic," 16 by applying specified information from the published literature and various disease-and populationbased databases.…”
Section: Box 1: Human Genome Variationmentioning
confidence: 99%
“…Главной целью сбора и анализа фармакогенетической информации в настоящее время является возможность оптимизации терапии -выбор препарата, который улучшил бы соотношение риска и пользы для конкретного пациента. В одной из описанных ранее когорт 95 из 98 детей имели по крайней мере один клинически значимый фармакогеномный вариант, следовательно, превентивный фармакогенетический скрининг может способствовать безопасности пациентов [24].…”
Section: обмен опытомunclassified
“…While these exome cases did not meet criteria for Stavropoulos' technical comparison study, outcome data prompted by WES result disclosure remain relevant to the study reported here. As well, while pharmacogenomics variants were identified in this cohort [41], medical management implications of these variants were not captured because identified variants had not been validated or reported back to patients at the time these data were ascertained. The absence of cascade family testing is surprising, but perhaps attributable to de novo findings or the absence of documentation related to cascade family testing in the proband's medical record.…”
Section: Disscussionmentioning
confidence: 99%